Evangelization and the Catholic Identity of Medical Schools - Pellegrino, Edmund D. (Medicina e Morale, 1992)
John Paul II, in his Apostolic Constitution for Catholic Universities, selected evangelization as one of the distinctive characteristics of Catholic universities. The author argues that evangelization of a kind proper to a medical school is essential to its Catholic identity; that properly construed evangelization can enhance, rather than diminish, the quality of medical education and patient care; and that without being part of the Church's evangelizing mission, Catholic medical schools cannot withstand the powerful currents which now tug them in the direction of secularization.